The Effect of Micro and Macroeconomic on Investment Opportunity: Evidences in ASEAN Countries - Adiputra, I Gede; Affandi, Azhar (Management Institute Faculty of Economics Universitas Andalas, 2018)
The purpose of this study is to obtain results: the influence of micro and macroeconomic factors of the company on investment opportunities. This research is conducted in five ASEAN countries, such as; Indonesia, Malaysia, Singapore, Thailand, and the Philippines (ASEAN-5). The microeconomic factors are measured by firm size, financial risk, profitability, and debt policy. The macroeconomic factors are measured by interest rates, exchange rates, inflation, and economic growth. The analysis unit of this study is 175 large capacity manufacturing industries listed on ASEAN-5 stock exchanges for the 2012-2017 period. The data analysis technique used is panel data regression analysis. The result shows that the Debt Equity Ratio has a negative and significant effect on investment opportunities in Microeconomic influence for the ASEAN-5 Countries. Risk does not have a significant effect on investment opportunities. Profitability is insignificant for the ASEAN-5 Countries and is significant for the State of Singapore, Thailand. Firm Size is significant for Indonesia, Malaysia, Singapore, and the Philippines. GDP growth has a significant effect on investment opportunities for the ASEAN-5 countries. The interest rate has harmed the opportunities of investment in Indonesia, Malaysia, and Singapore. Inflation has a negative and significant effect in Indonesia, Malaysia, Thailand, and the Philippines. Exchange rates are significant for Indonesia, Malaysia, and Singapore. Investment opportunities have a positive effect on the value of the company in ASEAN-5 Countries. The benefits of this study for creditors are as a guideline for disbursing credit, and for investors it is as a guideline for placing capital investments in companies that have favorable debt and equity considerations in five (5) ASEAN Countries.